Supportive Care Needs in Glioma Patients and Their Caregivers in Clinical Practice: Results of a Multicenter Cross-Sectional Study - Renovanz, Mirjam; Maurer, Dorothea; Lahr, Heike; Weimann, Elke; Deininger, Monika; Wirtz, Christian Rainer; Ringel, Florian; Singer, Susanne; Coburger, Jan (Frontiers in Neurology, 2018)
Objective: Supportive care needs in glioma patients often remain unrecognized, and optimization in assessment is required. First, we aimed at assessing the support needed using a simple structured questionnaire. Second, we investigated the psychosocial burden and support requested from caregivers. Methods: Patients were assessed at three centers during their outpatient visits. They completed the Distress Thermometer (DT; score ≥ 6 indicated significant burden in brain tumor patients), the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ)-C30+BN20, and the Patients’ Perspective Questionnaire (PPQ) that assessed psychosocial distress as well as support requested and received by patients for specific domains. In each subgroup, patients’ caregivers were assessed simultaneously by a questionnaire developed for the study. Multivariate backward logistic regressions were performed for investigating predictors of patients’ request for support. Results: Assessments were conducted for 232 patients. Most patients (82%) had a high-grade glioma and a mean age of 52 years (range 20–87). The male to female ratio was 1.25:1. According to the PPQ results, 38% (87) of the patients felt depressed; 44% (103), anxious; and 39% (91), tense/nervous. Desired support was highest from doctors (59%) and psychologists (19%). A general request for support was associated with lower global health status (p = 0.03, odds ratio (OR) = 0.96, 95% CI: 0.92–0.99) according to EORTC QLQ-C30. Most of the assessed caregivers (n = 96) were life partners (64%; n = 61) who experienced higher distress than the corresponding patients (caregivers: 6.5 ± 2.5 vs. patients: 5.3 ± 2.4). When patients were on chemotherapy, caregivers indicated DT ≥ 6 significantly more frequently than patients themselves (p = 0.02). Conclusion: Our data showed that glioma patients and their caregivers were both highly burdened. The PPQ allowed us to evaluate the psychosocial support requested and perceived by patients, detect supportive care needs, and provide information at a glance. Patients in poorer clinical condition are at risk of having unmet needs. The caregivers’ burden and unmet needs are not congruent with the patients’ need for support. In particular, caregivers of patients on chemotherapy were more highly burdened than patients themselves.